A GLIMPSE OF THE PEOPLE OF ALTICA: OSTEOLOGICAL AND ISOTOPIC/RADIOCARBON ANALYSIS. Issue 2 (2019) - Storey, Rebecca; Buckley, Gina M.; Kennett, Douglas J.
Abstract: Altica is a rare first-farming village site in the Basin of Mexico that has survived to modern times. Thus, it provides a glimpse into life during the Early–Middle Formative period. While valuable archaeological information on the village was recovered in excavation, only four burials comprising four individuals were recovered, a very small sample. Two individuals are older-aged females; the third, a middle-aged male, was accompanied by prestigious nonperishable goods and indicates that there are status differences even at this early date. The final individual was a young male buried in a deviant manner, suggesting possible foul play. While all individuals have indicators of periods of poor health, stable isotopes of carbon and nitrogen paint a more complete picture of the types of foods these individuals consumed over their lifetime. Radiogenic strontium isotopes of tooth enamel identify one individual, the young male buried in a deviant manner, as non-native to the Altica region. Thus, there is mystery in the manner of death, but even in this small sample, the wider connections Altica had that are so evident in the artefactual analysis are found in the skeletons. In addition, accelerator mass spectrometry radiocarbon dating provides a chronology of occupation through the people.